THE SYMPTOM OF A VERTICAL FOLD AT THE ORTHODONTIC TEETH MOVEMENT TO THE POSTEXTRACTIONAL AREA - Sergei Vladimirovich Dmitrienko; Michael Olegovich Kovalev; Dmitriy Sergeevich Dmitrienko; Ernessa Grigorevna Vedeshina; Elena Aleksandrovna Ogonyan (Современная наука и инновации, 2022)
The study determines the main complications of orthodontic teeth movement to the post-extraction space. The most frequent complications were incomplete closure of interdental spaces and non-parallel root position after orthodontic treatment. The main reason of complications was gingiva mucosa fold in the post-extraction area, which was determined as «the symptom of a vertical fold of a post-extraction space».